The Influence of the Project-Based Learning Model on the Learning Outcomes of Fifth Grade Students in Science at Elementary School 01 Baru Cijantung, East Jakarta - Prasetyo Agung Wibowos; Trisni Handayani (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the effect of the Project-Based Learning (PjBL) model on the learning outcomes of fifth-grade students in science subjects at Elementary School 01 Baru Cijantung, East Jakarta. The research involved two groups: a control class receiving conventional instruction and an experimental class taught using the PjBL model. The results indicate that students in the experimental group achieved higher scores and demonstrated better engagement compared to those in the control group. Statistical tests confirmed a significant influence of PjBL on student learning outcomes. These findings suggest that the PjBL method enhances not only academic achievement but also critical thinking and problem-solving skills in science subjects. The study encourages the integration of PjBL in the elementary school curriculum to improve student learning experiences.